2000
DOI: 10.1103/physrevd.63.027502
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic deviation in Kaluza-Klein theories

Abstract: We study in detail the equations of the geodesic deviation in multidimensional theories of KaluzaKlein type. We show that their 4-dimensional space-time projections are identical with the equations obtained by direct variation of the usual geodesic equation in the presence of the Lorentz force, provided that the fifth component of the deviation vector satisfies an extra constraint derived here.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 7 publications
3
40
0
Order By: Relevance
“…This approach, has been already used for studying the Lorentz force equation in General Relativity (see for instance [4]) but a result, a la Avez and Seifert, for the Lorentz force equation was still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, has been already used for studying the Lorentz force equation in General Relativity (see for instance [4]) but a result, a la Avez and Seifert, for the Lorentz force equation was still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Geodesics deviations in vacuum space-times, namely, Schwarzschild and Reissner-Nordström space-times, are rigorously studied in [11]- [17]. Some studies on geodesic deviation can be found in [18]- [20]. Ghosh and Kar [21] investigated geodesic motion and geodesic deviation in warped space-times with a a time dependent extra dimension.…”
Section: Introductionmentioning
confidence: 99%
“…An approach conceived to study directly the physical question (Q) started in [17], [29], where the authors considered the solutions to the LFE as projections of suitable lightlike geodesics for a Kaluza-Klein metric. It is well known the relation between the LFE and the projections of timelike geodesics for a higher dimensional Kaluza-Klein spacetime [21][22][23][24]27,28]. However, it proved more useful for question (Q) to consider the solutions of the LFE as projections of lightlike geodesics in a Kaluza-Klein spacetime with a scale factor (for the additional dimension) proportional to the charge-to-mass ratio.…”
Section: Known Results On (Q)mentioning
confidence: 99%